Enhanced silk production and pupal weight in Bombyx mori through CRISPR/Cas9-mediated circadian Clock gene disruption - Daniel J. Brady; Alessio Saviane; Matteo Battistolli; Irene Varponi; Federica Barca; Kunihiro Shiomi; Silvia Cappellozza; Federica Sandrelli (PLoS ONE, 2025)
The domesticated silkworm, Bombyx mori, is crucial for global silk production, which is a significant economic activity supporting millions of livelihoods worldwide. Beyond traditional silk production, the growing demand for insect larvae in cosmetics, biomedical products, and animal feed underscores the need to enhance B. mori productivity. This study investigates the role of the circadian clock gene Clock in B. mori using CRISPR/Cas9-mediated mutagenesis to establish the ClkΔ29 knock-out mutant strain. Dysregulation of the circadian clock in ClkΔ29 was demonstrated by altered temporal transcriptional profiles of core circadian clock genes in adult heads and disrupted circadian-controlled behaviors, including adult eclosion and egg hatching rhythms under constant darkness. By analysing larval development timing, as well as the weights of late instar larvae, pupae, and cocoon components in ClkΔ29 mutants and in ClkΔ1922 silkworms (carrying an independently generated Clk- null allele), we showed that CLK contributes to physiological processes regulating B. mori development and growth. Importantly, ClkΔ29 mutants reared on a standard sericulture diet exhibited significant increases in key economic traits, with silk production increasing by up to 7%, and pupal weight increasing by up to 25% compared to wild-type controls. This study highlights the potential of circadian clock gene manipulation to significantly enhance sericultural productivity. Future research should focus on elucidating the molecular mechanisms driving these phenotypes and determining whether they result from circadian clock functions or pleiotropic effects of B. mori Clk. These findings provide a foundation for advancing sustainable sericulture and developing new commercial applications for silkworm-derived products.